Handbook of High‐resolution Spectroscopy 2011
DOI: 10.1002/9780470749593.hrs042
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Fourier Transform Infrared Spectroscopy

Abstract: Recent developments and applications of high‐resolution Fourier transform spectroscopy are reviewed. A short historical summary of the development of high‐resolution interferometric Fourier transform infrared (FTIR) spectrometers is given and the possibilities of the currently most highly resolving FTIR spectrometers, including a current prototype built for the Zürich group at the Swiss Light Source SLS as a synchrotron light source, are discussed. A short description of the principles of FTIR spectroscopy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 238 publications
0
42
0
Order By: Relevance
“…Another spectroscopic technique which relies on Fourier transformations is interferometric Fourier-transform spectroscopy, which is related, but not identical to time-resolved spectroscopy. The principles and applications of interferometric Fourier-transform spectroscopy are described in Albert et al (2010).…”
Section: A) Response To An Impulsion δ(T)mentioning
confidence: 99%
See 2 more Smart Citations
“…Another spectroscopic technique which relies on Fourier transformations is interferometric Fourier-transform spectroscopy, which is related, but not identical to time-resolved spectroscopy. The principles and applications of interferometric Fourier-transform spectroscopy are described in Albert et al (2010).…”
Section: A) Response To An Impulsion δ(T)mentioning
confidence: 99%
“…When one has a true intramolecular process leading to a homogeneous Lorentzian line shape combined with inhomogeneous Doppler line shape one finds a shape from convolution of the two functions, a Voigt line shape (see Albert et al (2010)). Sometimes, with very good data, the individual homogenous and inhomogeneous contributions can be separately evaluated (see for instance Hippler et al (2007) for an example).…”
Section: Other Sources Of Line Broadeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of synchrotron radiation sources has greatly enhanced the possibilities of highest resolution Fourier Transform Infrared spectroscopy of polyatomic molecules [1][2][3][4][5][6][7][8][9][10][11]. In recent work we have shown that the infrared spectra of molecules as complex as naphthalene [3], azulene [8] and indene [10] can be rotationally resolved and analyzed, which can help the search for the spectra of such molecules in an astrophysical context.…”
Section: Introductionmentioning
confidence: 99%
“…In an FT spectrometer, the intensity variation of the output beam is measured while scanning an interferometer delay line whose longest optical path determines the spectral resolution of the device, with the latest developments [4] reaching a resolution limit of 0.0005 cm −1 as a result of an optical delay of 11.7 m. Resolutions up to 100 kHz have also been demonstrated with frequency comb FT spectrometers [5]. FT spectrometers benefit from a large radiant throughput (étendue), which is an intrinsic property of a Michelson interferometer [6,7] and can be readily combined with extreme laser sources of petawatt-power ultrashort pulses [8], allowing a precise characterization of chemical compounds that could shed light on some current astrophysical problems [9,10].…”
mentioning
confidence: 99%